2016
DOI: 10.1002/eqe.2772
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incident angles of P waves on the dynamic responses of long lined tunnels

Abstract: Summary The impact of the incident angle of earthquake motion on the seismic response of the long lined tunnels is studied. Based on the time‐domain finite element method with the viscous‐spring artificial boundary condition, the earthquake motion of oblique incidence is transformed into the equivalent nodal forces acting on the truncated boundary of finite element model. In the present work, the formulas of equivalent nodal forces for the plane P wave with arbitrary incident angle are deduced and implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Recently, many artificial boundary conditions have been proposed [39][40][41], among them, the viscous-spring artificial boundary has attracted more attention [42][43][44] due to its good stability and high accuracy, which takes into account the elastic resilience of the medium and overcomes the low-frequency instability of the viscous boundary. As shown in Figure 3, the essence of the viscous-spring artificial boundary is a parallel spring-dashpot system with continuous distribution applied on the boundary node, the coefficient of the spring and the coefficient of damping can be expressed as follows [13]: In addition, the peak accelerations of six seismic records were uniformly adjusted to 0.2 g in order to avoid being affected by earthquake amplitude, and Table 1 shows the properties of selected seismic records. Figure 1 shows the time-history curves of acceleration, velocity, and displacement of seismic records.…”
Section: The Viscous-spring Artificial Boundarymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, many artificial boundary conditions have been proposed [39][40][41], among them, the viscous-spring artificial boundary has attracted more attention [42][43][44] due to its good stability and high accuracy, which takes into account the elastic resilience of the medium and overcomes the low-frequency instability of the viscous boundary. As shown in Figure 3, the essence of the viscous-spring artificial boundary is a parallel spring-dashpot system with continuous distribution applied on the boundary node, the coefficient of the spring and the coefficient of damping can be expressed as follows [13]: In addition, the peak accelerations of six seismic records were uniformly adjusted to 0.2 g in order to avoid being affected by earthquake amplitude, and Table 1 shows the properties of selected seismic records. Figure 1 shows the time-history curves of acceleration, velocity, and displacement of seismic records.…”
Section: The Viscous-spring Artificial Boundarymentioning
confidence: 99%
“…On the basis of Equation 3, this method has been extended to obliquely incident P waves. According to the research results of previous scholars [12,13,46,47], the principles of the wave input method are integrated and redefined according to the previous formulas. The obliquely incident P waves shear and squeeze when passing through the boundary, and therefore they not only generate reflected P waves but also reflected SV waves, assuming that incident P waves propagate obliquely from the bottom left corner, i.e.…”
Section: The Viscous-spring Artificial Boundarymentioning
confidence: 99%
See 1 more Smart Citation
“…Naggar et al [30] investigated the effects of the seismic input angle on the moments and thrusts of cylinder tunnel linings by a proposed analytical procedure. An input method of P waves and SV waves was proposed by Huang et al [24,31] to analyze the impacts of incident angles on the seismic behaviors of the lined tunnel. More relevant works can be found in [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Several strong earthquake events, such as the 1999 Chi-Chi Earthquake [1], the 1999 Turkey Koceali Earthquake [2], the 2004 Mid-Niigata Prefecture Earthquake [3,4], and the 2008 Wenchuan Earthquake [5][6][7], demonstrated that those tunnels may suffer different levels of seismic damage, ranging from lightly cracking to severely collapse. Therefore, the seismic stability of the tunnels in seismically active areas becomes an important engineering problem and arouses much attention [8].…”
Section: Introductionmentioning
confidence: 99%